Wilayah Kajian dan Filsafat Ekonomi Islam - Khoiruddin Nasution (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
This article attempts to study of both the area of Islamic economy and the philosophy of Islamic economy. In this paper, the researcher uses the data from al Qur 'an, prophet tradition, alfiqh and other resources, and then it will he analyzed by the hermeneutic approach The result of this paper, is that the area of Islamic economy including in social affairs (mu'amalah) field, while the philosophy of Islamic economy is the ideas of Islamic economy that presents the system of economy which guarantee the justice and the equality for every body who participates in economy activities.